Competitive interactions between C. albicans, C. glabrata and C. krusei during biofilm formation and development of experimental Candidiasis - Rossoni, Rodnei Dennis [UNESP]; Barbosa, Júnia Oliveira [UNESP]; Vilela, Simone Furgeri Godinho [UNESP]; Santos, Jéssica Diane dos [UNESP]; Barros, Patrícia Pimentel de [UNESP]; Prata, Márcia Cristina de Azevedo; Anbinder, Ana Lia [UNESP]; Fuchs, Beth Burgwyn; Jorge, Antonio Olavo Cardoso [UNESP]; Mylonakis, Eleftherios; Junqueira, Juliana Campos [UNESP] (Public Library Science, 2015)
In this study, we evaluated the interactions between Candida albicans, Candida krusei and Candida glabrata in mixed infections. Initially, these interactions were studied in biofilms formed in vitro. CFU/mL values of C. albicans were lower in mixed biofilms when compared to the single biofilms, verifying 77% and 89% of C. albicans reduction when this species was associated with C. glabrata and C. krusei, respectively. After that, we expanded this study for in vivo host models of experimental candidiasis. G. mellonella larvae were inoculated with monotypic and heterotypic Candida suspensions for analysis of survival rate and quantification of fungal cells in the haemolymph. In the groups with single infections, 100% of the larvae died within 18 h after infection with C. albicans. However, interaction groups achieved 100% mortality after 72 h of infection by C. albicans-C. glabrata and 96 h of infection by C. albicans-C. krusei. C. albicans CFU/mL values from larvae hemolymph were lower in the interacting groups compared with the monoespecies group after 12 h of infection. In addition, immunosuppressed mice were also inoculated with monotypic and heterotypic microbial suspensions to induce oral candidiasis. C. albicans CFU/mL values recovered from oral cavity of mice were higher in the group with single infection by C. albicans than the groups with mixed infections by C. albicans-C. glabrata and C. albicans-C. krusei. Moreover, the group with single infection by C. albicans had a higher degree of hyphae and epithelial changes in the tongue dorsum than the groups with mixed infections. We concluded that single infections by C. albicans were more harmful for animal models than mixed infections with non-albicans species, suggesting that C. albicans establish competitive interactions with C. krusei and C. glabrata during biofilm formation and development of experimental candidiasis.